0
$\begingroup$

I'm facing the proof of a theorem stating that the sum of two absolutely continuous independent random variables is a new absolutely continuous random variable whose density is given by the convolution of the density functions of the variables. At the beginning I find this statement that I'm struggling to understand (consider that before this theorem we onlybhad the definition of A.C. random variable and independence of random variables).

Let $X_1, X_2$ be two absolutely continuous random variables, and $\rho_1(t), \rho_2(t)$ be their density. Let $Y=X_1+X_2$. Then $\mathbb{P}( Y \leq t )= \mathbb{P}( X_1+ X_2 \leq t ) = \int\limits_{-\infty}^{+\infty} \rho_1(t_1) \cdot \int\limits_{-\infty}^{t-t_1} \rho_2(t_2) dt_2 dt_1$

How did we get this last step?

$\endgroup$
1
$\begingroup$

$$P\{X_1+X_2 \leq t|X_1=t_1)=P\{X_2 \leq t -X_1|X_1=t_1)$$ $=\int_{-\infty} ^{t-t_1} \rho_2(t_2)dt_2.$ Now integrate w.r.t the distribution of $X_1$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.